Gambaran Possible selves Pada Remaja SMP - Desy Chrisnatalia (Jurnal Psikologi TALENTA, 2022)
Possible selves are the part of the self that describe a person’s future self. The developed cognitive abilities and hypothetical thinking in adolescence allow them to conceptualize and speculate about who they are and what they hope to be in the future. Possible selves consist of two selves, the expected self  (hoped-for possible selves ) and the feared self (feared possible selves). Possible selves can provide an overview of adolescent identity and what motivates their behavior at present. The relationship between possible selves and self-regulation had motivated many researchers to research possible selves in adolescents. The majority of research on possible selves in adolescents was conducted in Western countries, although social and cultural contexts also play a role in forming possible selves.  This study aims to obtain an overview of the possible selves of middle high school adolescents aged 13-15 years. The study has used a survei method using an open-ended question questionnaire to get data regarding the description of possible selves from the research participants. A total of 66 participants were asked to write down a description of their possible- selves; both hoped-for possible selves and feared possible selves . The results showed that most of the participants in the study had possible selves related to work/occupation and relationships/interpersonal functions.  The study has found that female participants have more interpersonal relations/functions category than men. On the other side, male participants have more occupational categories than females. None of the study participants had possible- selves regarding health; physical appearance, and sexuality Keywords: Possible selves ; Adolescent; Hoped-for possible selves ; Feared possible selves ; Self concept                                                                                                                                                                                               Possible selves  adalah bagian dari self yang memberikan gambaran tentang diri seseorang di masa depan. Kemampuan kognitif dan berpikir hipotetis  yang berkembang pada usia remaja memampukan remaja untuk mengkoseptualisasi dan berspekulasi  dan mampu berpikir secara hipotetis memampukan remaja untuk memikirkan siapa diri mereka dan harapan akan diri mereka di masa depan. Possible selves  terdiri dari dua aspek self, yaitu gambaran diri yang diharapkan di masa depan (hoped- for possible selves ) dan gambaran diri yang ditakutkan di masa depan (feared possible selves ). Gambaran diri remaja di masa depan dapat memberikan gambaran tentang identitas remaja dan hal-hal apa saja yang memotivasi perilaku remaja pada saat ini. Hal tersebut memotivasi banyak peneliti melakukan penelitian tentang possible selves  pada remaja. Mayoritas penelitian tentang possible selves  pada remaja dilakukan di negara Barat walaupun konteks sosial dan budaya turut memiliki peran dalam pembentukan possible selves. Penelitian ini bertujuan untuk mendapatkan gambaran tentang possible selves  remaja SMP usia 13-15 tahun. Metode survei dengan menggunakan kuesioner pertanyaan terbuka digunakan untuk mendapatkan data mengenai gambaran possible selves  dari partisipan penelitian. Sejumlah 66 partisipan penelitian diminta untuk menuliskan gambaran possible selves  mereka baik hoped- for possible selves  dan feared possible selves. Hasil penelitian menunjukkan bahwa mayoritas remaja laki-laki dan perempuan dalam penelitian memiliki possible selves yang bekaitan dengan pekerjaan dan relasi/fungsi interpersonal. Namun demikian,  kategori relasi/fungsi interpersonal lebih banyak ditemukan pada perempuan daripada laki-laki dan kategori pekerjaan lebih banyak ditemukan pada remaja laki-laki.  Tidak satupun partisipan penelitian yang memiliki possible selves  dalam hal kesehatan fisik, penampilan fisik, dan seksualitas. Kata Kunci: Possible selves ; Remaja; Hoped-for possible selves ; Feared possible selves ; Konsep diri